DHA Supplementation Attenuates MI-Induced LV Matrix Remodeling and Dysfunction in Mice - Habicht; Mohsen, G.; Eichhorn, Lars; Frede, S.; Weisheit, C.; Hilbert, T.; Treede, H.; Gresir, E.; Duerr, G. D.; Velten, Markus; Dewald, Oliver (Oxidative Medicine and Cellular Longevity, 2020)
Objective. Myocardial ischemia and reperfusion (I/R) injury is associated with oxidative stress and inflammation, leading to scar development and malfunction. The marine omega-3 fatty acids (ω-3 FA), eicosapentaenoic acid (EPA), and docosahexaenoic acid (DHA) are mediating cardioprotection and improving clinical outcomes in patients with heart disease. Therefore, we tested the hypothesis that docosahexaenoic acid (DHA) supplementation prior to LAD occlusion-induced myocardial injury (MI) confers cardioprotection in mice. Methods. C57BL/6N mice were placed on DHA or control diets (CD) beginning 7 d prior to 60 min LAD occlusion-induced MI or sham surgery. The expression of inflammatory mediators was measured via RT-qPCR. Besides FACS analysis for macrophage quantification and subtype evaluation, macrophage accumulation as well as collagen deposition was quantified in histological sections. Cardiac function was assessed using a pressure-volume catheter for up to 14 d. Results. DHA supplementation significantly attenuated the induction of peroxisome proliferator-activated receptor-α (PPAR-α) (2.3±0.4 CD vs. 1.4±0.3 DHA) after LAD occlusion. Furthermore, TNF-α (4.0±0.6 CD vs. 1.5±0.2 DHA), IL-1β (60.7±7.0 CD vs. 11.6±1.9 DHA), and IL-10 (223.8±62.1 CD vs. 135.5±38.5 DHA) mRNA expression increase was diminished in DHA-supplemented mice after 72 h reperfusion. These changes were accompanied by a less prominent switch in α/β myosin heavy chain isoforms. Chemokine mRNA expression was stronger initiated (CCL2 6 h: 32.8±11.5 CD vs. 78.8±13.6 DHA) but terminated earlier (CCL2 72 h: 39.5±7.8 CD vs. 8.2±1.9 DHA; CCL3 72 h: 794.3±270.9 CD vs. 258.2±57.8 DHA) in DHA supplementation compared to CD mice after LAD occlusion. Correspondingly, DHA supplementation was associated with a stronger increase of predominantly alternatively activated Ly6C-positive macrophage phenotype, being associated with less collagen deposition and better LV function (EF 14 d: 17.6±2.6 CD vs. 31.4±1.5 DHA). Conclusion. Our data indicate that DHA supplementation mediates cardioprotection from MI via modulation of the inflammatory response with timely and attenuated remodeling. DHA seems to attenuate MI-induced cardiomyocyte injury partly by transient PPAR-α downregulation, diminishing the need for antioxidant mechanisms including mitochondrial function, or α-to β-MHC isoform switch.
CRIS-Team Scopus Importer:2022-05-03